Determining Large Trees and Population Structures of Typical Tree Species in Northeast China - Yutong Yang; Zhiyuan Jia; Shusen Ge; Yutang Li; Dongwei Kang; Junqing Li (Diversity, 2025)
Specialized research on large trees in Northeast China is rare. To strengthen the understanding of local large trees, a survey of 4055 tree individuals from 75 plots in southeastern Jilin Province was conducted. The individual number and species composition of large trees in the community, as well as large individual standards in diameter at breast height (DBH) and population structures of typical tree species, were analyzed. By setting a DBH ≥ 50 cm as the threshold, 155 individuals across all the recorded trees were determined as large trees in the community, and 32.9% (51/155) of them were national second-class protected plant species in China. By setting the top 5% in DBH of a certain tree species as the threshold of large individuals of that tree species, the large individual criteria of six typical tree species were determined. The proportion of basal area of large trees to all trees was 30.4%, and the mean proportion of basal area of large individuals across the six typical tree species was 23.9% (±4.0%). As for the population characteristics, Abies nephrolepis and Picea jezoensis had large population sizes but relatively thin individuals, Tilia amurensis and Pinus koraiensis had small population sizes but relatively thick individuals, while Betula costata and Larix olgensis had medium population sizes and medium-sized individuals.